Ethnocultural technologies of vocal training of students of pedagogical universities of China - Tingting, Zhang; Tagiltseva, Natalia G. (Edelweiss Applied Science and Technology, 2024)
The training of music teachers in China's pedagogical universities is based on strategies for linking national cultural traditions and innovative education systems in other countries. Today, special attention is paid to the training of music teachers, which is due to the increased demand of children and parents for music education. The deepening of such training is facilitated by the special specializations of students, which allow them to acquire knowledge and performing skills in a particular type of musical activity in the final semesters of study at the university. But, since students receive education in pedagogical universities, this performance training should be based on Chinese ethnocultural traditions, and be organically combined with pedagogical training. The article examines an ethnocultural technologist based on the traditions of the national Chinese opera, contributing to the formation of stage skills necessary both for staging an opera performance by students and for replenishing the pedagogical baggage of a school music teacher. The introduction of this technology into the "Performing Arts" subject of the "Vocal Music" specialization among fourth-year students has shown its effectiveness both for staging fragments of opera performances, not only by Chinese but also by Western composers and for replenishing the pedagogical skills of future music teachers.